FEASIBILITY REVIEW OF INVESTMENT DEVELOPMENT OF PARKING BUILDING ( Case Study At Telogorejo Hospital Semarang) - Wan Okto Ariyansah (International Conference on Coastal and Delta Areas, 2017)
Telogorejo Hospital Semarang is one of the centers of activities in the field of health services in the city of Semarang. The increasing number of patients, visitors, doctors, and employees using private vehicles resulted in increased volume of incoming vehicles, making it difficult to get adequate parking space. Lack of parking space causing inhibition of traffic flow, so require parking facility in the form of parking building. This study aims to analyze the characteristics of parking, parking space requirements and analyze the feasibility of investment in the construction of parking lots, especially in Telogorejo Hospital Semarang. so it can get the conclusion that the feasibility of investment in building parking Parking Hospital Telogorejo Semarang either this can be seen from the results of Telogorejo Hospital Analysis Semarang using BCR method to get the value of 1.41. Value 1.41> 1 which means the project is feasible to be implemented, because it has a high benefit value. And using the NPV method generated profit obtained is Rp. 41,622,088,410 The value of profits obtained is not so great but there is no minus (loss). Using the IRR method generated 15.58% which is above the provisions of BAPPENAS that is equal to 15.58%. Keywords: Feasibility, Investment of Parking Building Construction